MOF-modified polyester fabric coated with reduced graphene oxide/polypyrrole as electrode for flexible supercapacitors. (10th March 2020) - Barakzehi, Marjan; Montazer, Majid; Sharif, Farhad; Norby, Truls; Chatzitakis, Athanasios
Abstract: The interest in wearable supercapacitors has been flourishing in both the scientific and industrial fields. Here, daily-used polyester fabric (PET) is modified by using an Al-based MOF, namely MIL-53(Al), via a layer-by-layer assembly method at room temperature. Then, reduced graphene oxide is deposited on the PET/MOF surface through dip coating in a graphene oxide suspension, followed by chemical reduction. Ultimately, pyrrole is polymerized on the surface of the PET/MOF/rGO surface by an in situ chemical polymerization process. The obtained composite is used as electrode achieving an areal capacitance of 510 mF cm −2 at a scanning rate of 1 mV s −1 in an aqueous H2 SO4 electrolyte. The optimized electrode is employed in a symmetrical solid-state-supercapacitor device, which delivers a volumetric capacitance of 3.5 F cm −3, energy density of 64 μW h cm −3 and power density of 0.6 mW cm −3 . The symmetrical device shows a good cycling stability even after 12 months storage in ambient conditions retained 85% of the initial capacitance after 1000 voltammetric cycles. Graphical abstract: Image 1